Urban agriculture in Baltimore, Maryland: Documenting current irrigation practices and rainwater harvesting - Abriana Segal; Niya Khanjar; Julie Yang; Kelsey Brooks; Marcus Williams; Neith Little; Andrew Lazar; Rachel E. Rosenberg Goldstein (Urban Agriculture & Regional Food Systems)
Abstract Rainwater harvesting could address freshwater shortages impacting urban agriculture caused by climate change. Limited studies exist on perceptions and concerns about using harvested rainwater for crop irrigation, and to our knowledge none have focused on urban agriculture. We surveyed urban farms and community gardens in Baltimore, Maryland, to document current irrigation practices and water sources and determine interest in rainwater harvesting. We evaluated differences in farm/garden characteristics and water uses between those harvesting rainwater, interested in rainwater harvesting, and not interested in rainwater harvesting. Most Baltimore farms/gardens surveyed were concerned about water availability (59%, n = 20), but all had access to city‐supplied water and only 14% (n = 5) reported water access preventing site expansion. Only 18% of sites used drip irrigation (n = 11), 89% (n = 33) were not using any water filtration, and most (72%, n = 23) had never attended a produce safety training. Twenty‐seven percent (n = 10) of sites were harvesting rainwater, 54% (n = 20) were interested in harvesting rainwater, and 19% (n = 7) were not interested. Ninety percent (n = 9) of the sites currently harvesting rainwater used covered rain barrels, an important strategy for preventing contamination. There were no significant associations between farm/gardens’ rainwater harvesting interests and farming practices, water access and use, or demographics of site respondents. Those currently harvesting rainwater and those interested had numerous concerns about rainwater harvesting including installation, design, and water quality, and were interested in additional information. Offering rainwater harvesting, food safety and education programs to urban farmers and gardeners could increase the safe use of this important water source.